Rotational barriers in N-benzhydrylformamides: An NMR and DFT study - Sadvakassova, Madina Zh; Khlebnikov, Andrei I.; Bakibaev, Abdigali A.; Kotelnikov, Oleg A.; Erkasov, Rakhmetulla Sh; Yelubay, Madeniyet A.; Issabayeva, Manar A. (Molecules)
N-Benzhydrylformamides are pharmacologically active compounds with anticonvulsant, enzyme-inducing, antihypoxic, and other types of biological activity. The conformational behavior of benzhydrylformamides is determined to a great extent by the presence of substituents at the nitrogen atom and in the ortho-position(s) of the diphenylmethane moiety. Particularly, the NMR spectra of these compounds often contain two sets of signals originating from different orientations of the formyl group. With the use of the dynamic NMR method and DFT calculations, we investigated the internal rotations of aromatic and formyl fragments and estimated the corresponding rotational barriers in N-benzhydrylformamide (BHFA), N-methyl-N-benzhydrylformamide (BHFA-NMe), and in a series of ortho-halogen-substituted N-benzhydrylformamides. It was found that the DFT method at M06-2X/6-311+G* level of theory satisfactorily reproduces the experimental barrier ΔG≠298(Formyl) of the formyl group rotation in BHFA-NMe. In BHFA, BHFA-NMe, and in the ortho-halogen derivatives, the calculated ΔG≠298(Formyl) values are close to each other and lie within 20–23 kcal/mol. On the other hand, the ortho-substituents significantly hinder the rotation of aryl fragment with ΔG≠298(Aryl) values varying from 2.5 kcal/mol in BHFA to 9.8 kcal/mol in ortho-iodo-N-benzhydrylformamide.